Prediction of borderline personality disorder based on childhood trauma with the mediating role of experiential avoidance - Jiang, Boliang (Frontiers in Psychiatry, 2024)
Introduction Traits of borderline personality disorder are important for the determination of the prognosis of mental illnesses and in evaluating risks of negativity as well as impulsivity. But, there is a lack of information about the distribution characteristics of borderline personality disorder traits and symptoms within clinical groups. The goal of the current study was to predict borderline personality disorder based on childhood trauma, using experiential avoidance as a mediator. Methods All male patients hospitalized in local psychiatric health centers with a diagnosis of borderline personality disorder comprised the statistical population of the current study. The number of 60 patients were selected by the purposeful sampling method. The questionnaire included the Childhood Trauma Questionnaire (CTQ), the Experiential Avoidance Questionnaire (AAQ-II), and the Borderline Personality Disorder Symptoms (BSL-23). Results and discussion The results demonstrated that there is a considerable and positive relationship between childhood trauma and experiential avoidance (r = 0.711, p< 0.01). In the mediating model, childhood trauma had significant direct predictive effects on borderline personality disorder (β = 0.546, p< 0.01). Also, between childhood trauma and BPD, experienced avoidance acts as a moderating factor. (β = 0.304, p< 0.01).